Understanding Sharia Processes Women's Experiences of Family Disputes - Ahmed, Farrah (Bloomsbury Academic, 2021)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com Sharia family law processes have attracted increasing debate and controversy in the United Kingdom, Canada and Australia in recent years. While the reasons for opposition to sharia processes are complex, they often feature the concern that sharia processes disadvantage Muslim women. However, to date there has been inadequate attention to the experiences of participants in sharia processes. This book studies women's experiences with these processes in Australia, with attention to the question of how religious communities and liberal legal systems can best respond to the needs of Muslim women who use these processes. In doing so, the book offers unique evidence to inform future policy developments in Australia that will also have implications for other liberal jurisdictions. In this way, the book makes a significant contribution to the international discussion and response to sharia processes.